The Role and Importance Of Modern Technologies In The Formation Of Oral Speech - Saydaliyeva, Mashkhura (Indonesian Journal Publisher, 2024)
The integration of modern technologies in language education has revolutionized the process of developing oral speech skills among learners. This article examines the role and importance of technological tools in enhancing oral speech formation, particularly in foreign language learning contexts. Additionally, the challenges of implementing modern technologies are addressed with suggested solutions. The findings suggest that a balanced approach combining traditional methods with modern technology significantly enhances oral speech development, empowering learners to communicate effectively in globalized settings.